The first fossils of Alloraphes (Coleoptera: Staphylinidae: Scydmaeninae) described from Miocene Dominican amber - Egan, Ben M.j.; Loewen, Elyssa; Mckellar, Ryan C. (Zootaxa, 2025)
Alloraphes Franz, 1980 is a small Neotropical genus (14 species) of Scydmaeninae (Coleoptera: Staphylinidae) beetles. Alloraphes are typically discriminated from the morphologically similar Stenichnaphes Franz via their aedeagal characteristics. Consequently, female members of both genera are often difficult to correctly place. Here we describe the first fossil species of Alloraphes in amber, and document its presence on the island of Hispaniola during the Miocene. Two individuals of new species Alloraphes cantusfurca sp. nov. are morphologically described using CT-scan data and microscope imagery. As the first known fossil member of the genus, A. cantusfurca provides a vital calibration point for future phylogenetic analysis and extends the temporal and geographic range of the genus. The implications for the biogeography of related taxa are also discussed.